Development of Indonesian Language Teaching Materials Based on Google Classroom in Primary Schools - Halidjah, Siti; Pranata, Rio (Journal of Education Technology, 2021)
The change from face-to-face learning to online learning makes it difficult for teachers to create good learning. This causes student learning outcomes to be low because students have difficulty in learning. This study aims to develop Google Classroom-based teaching materials suitable for learning Indonesian on theme 3 sub-theme 1 for grade IV in elementary schools. This type of research is development research that uses the ADDIE model. The research subjects are 3 experts from media expert validator, linguist validator, and learning design. The research sample was 32 students. The methods used to analyze the data are observation, interviews, and questionnaires. The instrument used in collecting data is a questionnaire. The technique used to analyze the research data is descriptive qualitative and quantitative analysis. The study results, namely the validation of design experts, showed an average number of 4.6, which was categorized as very valid; the expert validation of the learning video shows an average of 4.75, which is also classified as very valid. The results of video validation studies of linguists and experts also show very valid results with an average of 4.35 and 4.65, respectively. In addition, the results of expert validation of e-book learning and learning videos obtained an average score of 4.6 and 4.55, and both numbers are classified as very valid. Finally, the teacher's assessment of the practicality of teaching materials obtained an average of 3.45 and is classified as very practical. It can be concluded that Google Classroom-based teaching materials suitable for learning Indonesian are feasible to be applied in the learning process. This research implies that teachers' teaching materials can be used by teachers to facilitate students in learning Indonesian.